2016
DOI: 10.1002/cplu.201600214
|View full text |Cite
|
Sign up to set email alerts
|

Light on Chirality: Absolute Asymmetric Formation of Chiral Molecules Relevant in Prebiotic Evolution

Abstract: Homochirality is a distinct property of living matter manifested by the unichiral molecular units of genetic material and of proteins, namely, d‐deoxyribose and l‐amino acids. These molecular subunits or their precursors have been shown to form under various prebiotic conditions in racemic form. However, the nature of the chiral influence, which results in the first breakage of molecular symmetry, remains unclear. In this respect, the photochemical model of enantioselection has gained particular importance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 134 publications
2
26
0
Order By: Relevance
“…The racemic distributions of amines in the samples analyzed here, are consistent with the racemic compositions of analogous aliphatic monocarboxylic acids found in meteorites from various petrologic types (Aponte et al, 2014b) and with the measurements of racemic amines in the Murchison and Orgueil meteorites (Aponte et al 2014a;Aponte et al 2015). Additionally, our results are supported by anisotropy studies suggesting that ultra-violet circularly polarized light (UVCPL) may induce enantiomeric excess aliphatic amino acids, but not in amines and carboxylic acids (Meinert et al, 2011, Myrgorodska et al, 2016.…”
Section: Racemic Composition Of Chiral Amines and Isovaline The Enansupporting
confidence: 89%
“…The racemic distributions of amines in the samples analyzed here, are consistent with the racemic compositions of analogous aliphatic monocarboxylic acids found in meteorites from various petrologic types (Aponte et al, 2014b) and with the measurements of racemic amines in the Murchison and Orgueil meteorites (Aponte et al 2014a;Aponte et al 2015). Additionally, our results are supported by anisotropy studies suggesting that ultra-violet circularly polarized light (UVCPL) may induce enantiomeric excess aliphatic amino acids, but not in amines and carboxylic acids (Meinert et al, 2011, Myrgorodska et al, 2016.…”
Section: Racemic Composition Of Chiral Amines and Isovaline The Enansupporting
confidence: 89%
“…In the same line, Oró’s experiments showed that the addition of a mixture of HCN and NH 3 in a water solution yielded the formation of adenine (one of the four nitrogenous bases), whereas by adding H 2 CO in the mixture the synthesis of ribose and deoxyribose (the sugars that are part of the nucleotide) was observed, in agreement with the Butlerov formose reaction . These experiments paved the way for the development of a new field of research, that is, prebiotic chemistry, and since then many theories have attempted to explain how the complex machinery of life emerged on a primitive Earth and which energy sources could have helped start up the implicated processes, such as UV radiation, hydrothermal energies of the deep sea, meteorites as catalysts and their impact as a source of energy, and redox energies . In the last few years, this subject has been continuously growing and, nowadays, is covered not only by the prebiotic chemistry on Earth but also in the Universe .…”
Section: Introductionmentioning
confidence: 76%
“…57 Such an astrophysical scenario is supported by the discovery of partially-polarized CPL in large portion of space in heavy star formation regions such as the Orion Nebulae. 58,59 This major finding motivated several SR studies on UV/VUV asymmetric photochemistry in condensed matter [60][61][62] leading to a few % ee on amino-acids produced by asymmetric photochirogenesis from interstellar-analogue ices 63,64 and by CDdriven asymmetric photolysis from racemic thin films. 65,66 In a previous study on alanine, 33,34 we proposed PECD as an alternative asymmetric photophysical route in the gas phase for the production of ee in amino-acids in a given direction of space.…”
Section: Vaporisation Conditionmentioning
confidence: 97%